An analysis of parents' perception on the importance of homework: a case study in Malaysia - Abdullah, Hazlina; Abdullah, Norhana; Abdullah, Liza; Abdul Ghani, Noor Amili; Md Zamin, Ainul Azmin; Kassim, Rosnani (Science International, 2017)
Homework is often viewed as a crucial part of learning as it enhances children’s academic performance. Yet only a few studies to date have focussed specifically on the perceptions of parents regarding the importance of homework. Thus, this paper discusses the results of a study that sought to investigate a group of parents’ perceptions on the importance of homework within the Malaysian setting. Using a questionnaire survey containing the ways how parents get involved with their children’s homework, the parents’ perceptions with regard to the importance of homework were inferred. Findings suggest that parents show keen support towards homework, indicated through the responses of parental involvement they offer their children. A high percentage of parents view homework as important in all the three aspects: provision of structure, direct involvement, and autonomy support